3(2x+5)=4x+17

Simple and best practice solution for 3(2x+5)=4x+17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2x+5)=4x+17 equation:


Simplifying
3(2x + 5) = 4x + 17

Reorder the terms:
3(5 + 2x) = 4x + 17
(5 * 3 + 2x * 3) = 4x + 17
(15 + 6x) = 4x + 17

Reorder the terms:
15 + 6x = 17 + 4x

Solving
15 + 6x = 17 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
15 + 6x + -4x = 17 + 4x + -4x

Combine like terms: 6x + -4x = 2x
15 + 2x = 17 + 4x + -4x

Combine like terms: 4x + -4x = 0
15 + 2x = 17 + 0
15 + 2x = 17

Add '-15' to each side of the equation.
15 + -15 + 2x = 17 + -15

Combine like terms: 15 + -15 = 0
0 + 2x = 17 + -15
2x = 17 + -15

Combine like terms: 17 + -15 = 2
2x = 2

Divide each side by '2'.
x = 1

Simplifying
x = 1

See similar equations:

| x^2-x=12 | | 30=15k | | (2x+14)(x-3)=146 | | 9(X+5)=8X+37 | | 9(X+5)=8X | | (2x+14)(x-3)=111 | | 9x+4(-2x-7)=-19-8x | | 3(2z-5)=5(z+2) | | 1+2x=6+x | | 18(x-40)=36(x-30) | | 8x+12=77-5x | | 3(X-2)=6 | | 8(x-5)+3x=5(x+2) | | 7x-6x=19 | | 5(X-12)=-25 | | 5r+2r=0 | | 23+x=47 | | 7y+12=4y-(y+1) | | 3(X+6)=12 | | x^2y^2=2y^3-12 | | 5x-4=7x | | 4c-11=17 | | 9=1+5k-7k | | 21(x-12)=-21(x-26) | | 9x-9=6x | | 17(x-25)=-17+3(x+34) | | 7x-25=-88 | | -10-8x^2+5x^6-3x^3+x= | | (2x+14)(x-3)=90 | | 10=-3a+1 | | 3b-12=15 | | 4x^4+5x^3-7x^4= |

Equations solver categories